Sacred Tomb of Ju Pangola - Andries Kango (Lembaga Sembilan Tiga Community, 2019)
This study aims to analyze the perception of pilgrims on the sacred tomb of Ju Pangola. In the Gorontalo area, the shrine is widely visited by pilgrims, both local and overseas. Ju Pangola himself was a famous 16th-century Muslim scholar, teacher, and figurehead of Gorontalo. He was considered a guardian by the community so his tomb was widely visited especially during certain months, for example during the Rajab, Shaykh, and Ramadan months. This study is a field study, with a phenomenological analytic approach that will look at the pilgrim's perception of the sacred tomb of Ju Pangola. With qualitative analysis, this study seeks to produce descriptive data, a systematic, factual and accurate picture of the facts, the characteristics and the relationship between the observed phenomena. The results of this study revealed that the pilgrim's perception of Ju Pangola's tomb is as follows; first, that the tomb is capable of providing survival and survival. Secondly, that Ju Pangola is not an ordinary person but a guardian who can mediate their prayers to Allah Almighty. Third, that tombs can provide healing to the infectious disease usually through intermediary land graves or water that is prayed over the tomb. Fourth, that a pilgrimage could increase the trade if a trader diligently made a pilgrimage to the tomb of Ju Sangola. Fifth, pilgrims visit the tomb for a pilgrimage and pray for Ju Sangola.